Who is really 'left behind'? Half a century of gender differences in the school-to-work transitions of low-educated youth. (7th February 2021) - Struffolino, Emanuela; Borgna, Camilla
ABSTRACT: At a time of growing expectations about educational attainment, young people who did not complete upper-secondary schooling can easily be 'left behind' to face risks of social exclusion. Being able to make a rapid and successful transition into a first significant job is crucial for long-term labor-market attachment. We approach the question of continuity or change in school-to-work transitions by comparing the experiences of four birth cohorts of early school leavers in Italy, where they still constitute a sizeable group as of today. Italy makes for an interesting case study due to the length of school-to-work transitions and the extent of gender differences in this phase. In an era of educational expansion and increased female activation, studying changes in low-educated women's labor-market access brings into focus the question of who is really left behind. Using data from the 2009 'Multi-purpose Survey on Household and Social Subjects, ' we use discrete time logistic regression models to estimate the probability of transitioning to the first significant job for early school leavers born between 1954 and 1993. We find that gender differences are strikingly persistent across birth cohorts, even after controlling for sociodemographic variables as well as for time-varying fertility and partnership histories.